Selective Harmonic Elimination For A Single-Phase 13-Level TCHB Based Cascaded Multilevel Inverter Using FPGA - Abd Halim, Wahidah; Abd Rahim, Nasrudin; Azri, Maaspaliza (Korean Institute of Power Electronics (KIPE), 2014)
-